Radioactive Thoron 220Rn Exhalation From Unfired Mud Building Material Into Room Air of Earthen Dwellings - Nguyễn, Nguyệt Thị Ánh; Nguyễn-Thùy, Du’o’ng; Nguyễn-Văn, Hu’ó’ng; Nguyễn-Hải, Nam; Schimmelmann, Arndt (Frontiers in Earth Science, 2021)
Thoron (220Rn), an isotope of radon with a strong -decay energy, and its short-lived metallic progeny can pose an elevated lung cancer hazard in room air when unfired-soil derived building materials are used in earthen dwellings. Changes in moisture content and density influencing the thoron exhalation rate from earthen materials into room air were studied in the laboratory with terra rossa from a village on the Đồng Văn Karst Plateau Geopark, Việt Nam, where ethnic minorities construct traditional dwellings with unfired terra rossa walls and floors. Our results show that the thoron exhalation rate from mud surfaces depends on (i) the content of radioactive parental nuclides in mineral components; (ii) the moisture content of mud where ~5 to 10 weight % water maximizes the 220Rn exhalation rate; and (iii) the density of dry mud as primarily controlled by internal macroscopic voids, fractures, and porosity. Additional time-series of 220Rn exhalation data from an interior mud wall of a terra rossa-built house under different seasonal and weather conditions show that the temperature is influencing thoron exhalation via the water vapor pressure deficit (VPD) in air and the associated amount of atmospheric moisture adsorbed onto indoor mud surfaces. Our data suggest that occupants of ‘mud house’ earthen dwellings in northern Việt Nam are exposed to an increased thoron geohazard during cooler weather, low VPD, and high relative humidity in air. Detailed studies are needed to evaluate the thoron geohazard for inhabitants of mud-built dwellings in other climates and geological terrains.